Tasting Pseudomonas aeruginosa Biofilms: Human Neutrophils Express the Bitter Receptor T2R38 as Sensor for the Quorum Sensing Molecule N-(3-Oxododecanoyl)-l-Homoserine Lactone - Maurer, Susanne; Wabnitz, Guido H.; Kahle, Nadine A.; Stegmaier, Sabine; Prior, Birgit; Giese, Thomas; Gaida, Matthias Martin; Samstag, Yvonne; Hänsch, Gertrud Maria (Frontiers in Immunology, 2015)
Bacteria communicate with each other via specialized signalling molecules, known as quorum sensing molecules or autoinducers. The Pseudomonas aeruginosa-derived quorum sensing molecule N-(3-oxododecanoyl)-L-homoserine lactone (AHL-12), however, also activates mammalian cells. As shown previously, AHL-12 induced chemotaxis, up-regulated CD11b expression, and enhanced phagocytosis of polymorphonuclear neutrophils (PMN). Circumstantial evidence concurred with a receptor for AHL-12, which so far has been elusive. We investigated the bitter receptor T2R38 as a potential candidate. Although identified as a taste receptor, cells outside the gustatory system express T2R38, for example epithelial cells in the lung. We now detected T2R38 in peripheral blood neutrophils, monocytes and lymphocytes on the cell membrane, but also intracellular. In neutrophils, T2R38 was located in vesicles with characteristics of lipid droplets, and super-resolution microscopy showed a co-localisation with the lipid droplet membrane. Neutrophils take up AHL-12, and it co-localized with T2R38 as seen by laser scan microscopy. Binding of AHL-12 to T2R28 was confirmed by pull-down assays using biotin-coupled AHL-12 as bait. A commercially available antibody to T2R38 inhibited binding of AHL-12 to neutrophils, and this antibody by itself stimulated neutrophils, similarly to AHL-12. In conclusion, our data provide evidence for expression of functional T2R38 on neutrophils, and are compatible with the notion that T2R38 is the receptor for AHL-12 on neutrophils.